Experimental and theoretical study of field-dependent spin splitting at ferromagnetic insulator–superconductor interfaces - Machon, Peter; Wolf, Michael J.; Beckmann, Detlef; Belzig, Wolfgang (Beilstein Journal of Nanotechnology, 2022)
We present a combined experimental and theoretical work that investigates the magnetic proximity effect at a ferromagnetic insulator–superconductor (FI–S) interface. The calculations are based on the boundary condition for diffusive quasiclassical Green’s functions, which accounts for arbitrarily strong spin-dependent effects and spin mixing angles. The resulting phase diagram shows a transition from a first-order to a second-order phase transition for large spin mixing angles. The experimentally found differential conductance of an EuS-Al heterostructure is compared with the theoretical calculation. With the assumption of a uniform spin mixing angle that depends on the externally applied field, we find good agreement between theory and experiment. The theory depends only on very few parameters, mostly specified by the experimental setup. We determine the effective spin of the interface moments as J ≈ 0.74ℏ.
Keywords: circuit theory; magnetism; proximity effect; superconductivity; tunneling